Effect of Probiotics (EM-1) Addition on Quality Characteristics of Quail Meat - Mohd Fadzli Bin Nik Omar, Nik; Syazni Kamarudin, Ahmad; Huda, Nurul (International Journal of Engineering and Technology, 2018)
The objective of the present study is to see the effect of probiotics (EM-1) used in animal fed as supplement on the meat quality of quails. The quails that been used in this study was from breed Cortunix japonica. Along the study, the quails were divided into four groups which are control quails and quails that feed with 1 L probiotics in different ratio concentration drinking water (mL) (1:250, 1:500, and 1:750). After 42 days, all the quails were slaughtered and then the carcass and meat yield of each groups was determined. Then, the meat undergo physicochemical and nutritional analysis. The value of carcass yield both in male and female quails treated with EM-1 showed a higher significant differences (p < 0.05) compared to control quails and no significant differences (p < 0.05) were showed in meat yield. Significantly higher L* and pH values (p < 0.05) in whole leg, were found when quails were fed the EM-1 (1:500). While in cooked quail meats no significant different (p < 0.05) were showed in cooking loss, juiciness and shear force analysis between the treatments. In quail meat sausages no significant different (p < 0.05) were showed in cooking loss, juiciness, folding test and shear force analysis between the treatments but in texture profile analysis, treatments 1:500 showed significantly higher values (p < 0.05) of hardness, springiness and cohesiveness compared to other treatments. Addition of this probiotics are therefore contributed to some improvements in the meat quality.Â